2007
DOI: 10.1016/j.jtcvs.2006.06.051
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter trial of an intrabronchial valve for treatment of severe emphysema

Abstract: These first multicenter results with the Intrabronchial Valve demonstrate significant improvements in health-related quality of life and acceptable safety, ease of use, and procedural complication rates. The valve might be a safer and less-invasive alternative to surgical therapy for patients with severe emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 23 publications
4
105
0
1
Order By: Relevance
“…This may be achieved with one-way (expiratory) valves placed in the airways or by introduction of tissue glues (36)(37)(38)(39). In patients in whom atelectasis is achieved, mechanisms of improved lung function or symptoms are likely identical to those after surgical LVR.…”
Section: Physiologic Basis For Improvement After Bronchoscopic Lung Vmentioning
confidence: 99%
“…This may be achieved with one-way (expiratory) valves placed in the airways or by introduction of tissue glues (36)(37)(38)(39). In patients in whom atelectasis is achieved, mechanisms of improved lung function or symptoms are likely identical to those after surgical LVR.…”
Section: Physiologic Basis For Improvement After Bronchoscopic Lung Vmentioning
confidence: 99%
“…In recent years, new surgical and bronchoscopic lung volume reduction techniques have been proposed in an attempt to reduce the typical shortcomings of resectional LVRS [12][13][14][15]. We have developed a nonresectional LVRS technique in awake patients that respects the basic concepts of resectional LVRS but adds some theoretic advantages and can be performed solely with thoracic epidural anesthesia.…”
mentioning
confidence: 99%
“…It has the ability of obstructing the airflow selectively in the segments where it is placed and, by the same token, allows secretions to exit the segment. One study with 30 patients showed improvements in quality of life, however without significant differences in pulmonary function (Wood, McKenna et al 2007). This study has used outcome measures similar to LVRS.…”
Section: Devices and Resultsmentioning
confidence: 99%